The Psychological Damage Inflicted on the Accused and its Treatment In Islamic Jurisprudence And Law - Alo Hussein, Ihsan (Opción, 2019)
Recently, the development of youth entrepreneurship has received a con- siderable attention from both the literature and the governments. Yet, most studies focus on developed countries. Therefore, this study was based in the Malaysian context through developing social entrepreneurial training program to inculcate entrepreneurship skills and knowledge. This paper aimed to analyse the entrepreneurial training determinants that successfully formed entrepreneurial intention among secondary school teachers. A sur- vey via questionnaire was conducted among 73 teachers. Exploratory factor analysis and multiple regression analysis were utilized. The selected schools are among the large schools in the city and provide entrepreneurial knowl- edge, especially to students with disability. The findings yielded that knowl- edge of entrepreneurship positively affects students’ intention mediated by, norms, attitude and self-efficiency.